Measurement of inclusive π 0 production in hadronic Z 0 decays - Adam,W; Adye,T; Agasi,E; Ajinenko,I; Aleksan,R; Alekseev,GD; Allport,PP; Almehed,S; Alvsvaag,SJ; Amaldi,U; Amato,S; Andreazza,A; et al. (Zeitschrift Fur Physik C Particles and Fields, 1995)
An analysis is presented of inclusive π 0 production in Z 0 decays measured with the DELPHI detector. At low energies, π 0 decays are reconstructed by using pairs of converted photons and combinations of converted photons and photons reconstructed in the barrel electromagnetic calorimeter (HPC). At high energies (up to Mathematical expression) the excellent granularity of the HPC is exploited to search for two-photon substructures in single showers. The inclusive differential cross section is measured as a function of energy for qq and bb events. The number of π 0's per hadronic Z 0 event is N(π 0)/Z had 0 =9.2±0.2(stat)±1.0(syst) and for bb events the number of π 0's is N(π 0)/bb=10.1±0.4(stat)±1.1(syst). The ratio of the number of π 0's in bb events to hadronic Z 0 events is less affected by the systematic errors and is found to be 1.09±0.05±0.01. The measured π 0 cross sections are compared with the predictions of different parton shower models. For hadronic events, the peak position in the ξ p=ln(1/xp) distribution is ξ p =3.90 -0.14 +0.24 . The average number of π 0's from the decay of primary B hadrons is found to be N(B→π 0 X)/B hadron=2.78±0.15(stat)±0.60(syst). © 1996 Springer-Verlag.